The Socioeconomic Impacts of Agropolitan Project in the Rural Areas of the East Coast Region of Malaysia - Abdul Rahman Abdul Latip; Osman Md Yusoff; Mohamad Shaharudin Samsurijan (Kajian Malaysia, 2020)
In 2007, Kelantan and Terengganu were among the states with the highest poverty rates in Malaysia. The East Coast EconomicmRegion (ECER) Master Plan, approved by the Malaysian Government in 2008, was formulated as a basis to guide the development of ECER until 2020. It identifies projects and programmes to reduce regional socioeconomic disparities, eradicate poverty and improve income and wealth distribution in a sustainable manner. The Agropolitan Project is an integrated socioeconomic scheme initiated by ECER with the ultimate aim of eradicating poverty among the most impoverished communities within the region. This study aims to analyse the socioeconomic impacts of the Agropolitan Project that has been implemented in rural areas of Kelantan, Terengganu and Pahang. The study uses the quantitative method by administering a set of questionnaires to 97 respondents from the Agropolitan Project across the ECER states. It also uses the qualitative approach (in-depth interviews with ten key informants and two sessions of a focus group discussion) including direct observation, as well as desk-based research. This study found positive changes in some of the participant’s lives, with job opportunities and improvements to their standard of living. Nonetheless, more effort is needed to ensure that the project achieves its vital objectives.